Endotoxin removal and plasmid DNA recovery in various metal ion solutions - Ongkudon, C.; Danquah, Michael (Taylor and Francis, 2011)
In this brief article, we report endotoxin precipitation using different types of metal ion in plasmid DNA purification. The work involved modification and improvement of the LAL chromogenic analysis to compensate for metal ion-LAL interaction. Results (Figs. 1 and 2) show that ZnSO4 gives an optimum combination of high endotoxin removal efficiency (~91%) as well as high plasmid recovery (~100%) compared to other metal ions tested.